2010
DOI: 10.2478/v10042-009-0096-x
|View full text |Cite
|
Sign up to set email alerts
|

p21/Wafl/Cipl cellular expression in chronic long-lasting hepatitis C: correlation with HCV proteins (C, NS3, NS5A), other cell-cycle related proteins and selected clinical data.

Abstract: Studies indicate that proteins of hepatitis C virus (HCV) disturb expression of cell-cycle-related proteins. A disturbed cell-cycle control is a hepatocellular carcinoma (HCC) risk factor in patients with HCV-related liver damage. The present study aimed to analyse the cellular expression of p21/ Wafl/Cipl (p21) in long-lasting chronic hepatitis C (CH-C), its correlation with the key oncogenic HCV proteins (C, NS3, NS5A), other cell-cycle-related proteins (PCNA, Ki-67, cyclin D1, p53) and selected clinical dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Each tissue specimen of liver biopsy was evaluated based on a numerical scoring for the total grading of portal/periportal necroinflammation (G: 0–4), for the stage of fibrosis (S: 0–4) and liver steatosis (0–2), as described earlier [20]. The control group included serum samples from 10 healthy blood donors.…”
Section: Methodsmentioning
confidence: 99%
“…Each tissue specimen of liver biopsy was evaluated based on a numerical scoring for the total grading of portal/periportal necroinflammation (G: 0–4), for the stage of fibrosis (S: 0–4) and liver steatosis (0–2), as described earlier [20]. The control group included serum samples from 10 healthy blood donors.…”
Section: Methodsmentioning
confidence: 99%
“…Many studies have reported the specific molecular types, the subcellular localization, and particular domains of proteins influencing the oncogenic mechanisms. 18 The major risk factor for hepatocellular carcinoma (HCC) is a chronic HCV infection. 19 Studies have shown that one mechanism of hepatic oncogenesis is the interaction between the HCV oncogenic proteins and factors that either control cell proliferation or inhibit their apoptosis, while other studies have also confirmed that some viral proteins physically or functionally interact with the products of suppressor genes leading to the development of primary HCC.…”
Section: Discussionmentioning
confidence: 99%
“…The NS3 transforms mammalian cells but its role in HCC is less clear[ 94 , 95 ]. This protein interacts with tumor suppressor p53.…”
Section: Viral Factorsmentioning
confidence: 99%